C-shaped Canals in Mandibular Second Molars: A Cone Beam Computed Tomography Analysis - Hussain, Asdaq; Acharya, Nisha; Chakradhar, Anil; Naz, Shazia x; Zahra, Ambreen; Khatoon, Samina (Birat Journal of Health Sciences, 2025)
Introduction: A thorough grasp of possible anatomical variations is crucial for successful root canal treatment. An example of such a variation is the C-shaped canal morphology, primarily observed in mandibular second molars. This morphology is distinguished by a cross-sectional configuration resembling the letter “C.” Objective: This study aimed to assess the prevalence of C-shaped canals in permanent mandibular second molars among patients attending a tertiary care hospital in Nepal, utilizing cone-beam computed tomography (CBCT). Methodology: This descriptive cross-sectional study was conducted at the Department of Conservative Dentistry and Endodontics, Kathmandu University School of Medical Sciences (KUSMS) - Dhulikhel Hospital, Nepal, from December 2020 to November 2021. Ethical approval was obtained from the Institutional Review Committee of KUSMS prior to the study. CBCT scans of 150 mandibular second molars were evaluated by two endodontists. The study assessed tooth position (right or left side), prevalence of C-shaped canals, classification of C-shaped canal configurations at the orifice cross-sectional level, and the occurrence of C-shaped canals unilaterally or bilaterally. Data were analyzed using SPSS. Results: Out of the 150 teeth examined, 13 (8.7%) teeth exhibited a C-shaped root canal system. Among these 13 teeth, 7 (53.8%) teeth had an uninterrupted “C” configuration at the orifice level. Conclusions: This study found a notable prevalence of C-shaped root canals in mandibular second molars among the Nepalese population sampled.